Targeting Pin1 to overcome immunosuppressive tumor microenvironment in MSS colorectal cancer - Wang, Jian; Tang, Shuxin; Fan, Jinhua; Xiao, Huihui; Wang, Shihua; Xiang, Jianqin; Liu, Zhili; Liu, Hongying; Pei, Zhigang; Jiang, Dequan; Shuai, Leiyuan; Liu, Han; et al. (Frontiers in Immunology, 2025)
BackgroundManagement of the immunosuppressive tumor microenvironment (TME) is crucial for microsatellite stability (MSS) colorectal cancer (CRC), which responds poorly to immunotherapy. PIN1, a peptidyl-prolyl cis-trans isomerase that is overexpressed in human malignancies, regulates TME immunosuppression. However, its role in MSS CRC remains insufficiently explored.MethodsWe divided 411 CRC patients from the TCGA-COAD database into MSS or microsatellite instability-high (MSI-H) groups and analyzed their gene expression profiles. Using smoothed t-statistic SVM, weighted correlation network analysis, and sample clustering, we identified PIN1 as a key biomarker. We assessed Pin1 expression in CRC cell lines and tissues, and conducted functional assays, in vitro co-cultures, and in vivo studies (using a Pin1 inhibitor and anti-PD-1 in CT26 subcutaneous tumor and liver metastasis mouse models) to evaluate its effects and mechanisms.ResultsPIN1 was overexpressed in MSS CRC and negatively correlated with CD4+ T and CD8+ T cell infiltration. Knockdown of PIN1 in MSS CRC cells significantly reduced cell proliferation (assessed by CCK-8 assay), impaired migratory capacity (assessed via wound-healing assay), and increased the apoptotic rate (detected by flow cytometry). In CT26 mouse models, combining Pin1 inhibition with PD-1 blockade enhanced immunotherapy efficacy by reducing Treg infiltration, suppressing cancer-associated fibroblast (CAF) activity, and promoting CD8+ T cell recruitment. Mechanistically, PIN1 activated the NF-κB pathway and modulated CCL3-CCR5 signaling, which are critical for Treg migration and CAF activation.ConclusionOur findings suggest that Pin1 reshapes the immunosuppressive TME in MSS CRC through the NF-κB-CCL3-CCR5 axis, driving CRC progression and immunotherapy resistance. This pathway presents a potential target for overcoming immunotherapy resistance in MSS CRC.